A polarization independent quasi-TEM metamaterial absorber for X and ku band sensing applications - Hoque A.; Islam M.T.; Almutairi A.F.; Alam T.; Singh M.J.; Amin N. (MDPI AG, 2023)
Computer software; Electromagnetic waves; Metamaterials; Mirrors; Radar systems; Satellite communication systems; Absorber; Dual Band; Quasi-TEM; Sensing; X bands; Absorption spectroscopy